Long-term effects of tocilizumab on retinal and choroidal inflammation in Birdshot uveitis - Lynn S. zur Bonsen; Daniel Schulze; Steffen E. Künzel; Anne Rübsam; Uwe Pleyer; Dominika Pohlmann (Journal of Ophthalmic Inflammation and Infection)
Abstract Background Tocilizumab (TCZ), an interleukin-6 receptor antagonist, is approved for treating rheumatic diseases and has demonstrated efficacy in managing refractory non-infectious uveitis (NIU). This retrospective study aimed to investigate the long-term effects of TCZ on inflammation in the retinal and choroidal compartments in Birdshot NIU. Methods Eight patients (16 eyes) received TCZ and were included in the analysis. The primary outcomes measured were inflammatory activity in the retina and choroid, assessed by fluorescein angiography (FA) and indocyanine green angiography (ICGA) using the Angiography Scoring for Uveitis Working Group at baseline, 6, 12, 24, and 36 months. Results The mean follow-up time with TCZ treatment was 33 months. At baseline, the median FA score was 14 (quartiles: 10.25, 15.25), which significantly decreased over time (at 36 months: 8 (5.5, 11); p = 0.004). In contrast, the ICGA score significantly increased within the first year (median at baseline: 5 (4.75, 7.25); at 6 months: 7 (6, 9.25); at 12 months: 7 (6.5, 9.25); p = 0.002), but returned to baseline levels after two years (at 24 months: 5 (5, 6.5); at 36 months: 5.5 (4, 7.5)). Central retinal thickness (CRT) improved significantly after 6 months (median at baseline: 295 µm (275, 322); at 6 months: 275 µm (251, 308); p = 0.01). Conclusion TCZ is effective in reducing retinal vasculitis and CRT in refractory Birdshot uveitis over time, but might be less effective in managing choroidal inflammation. Further studies are needed to determine the optimal treatment strategies for TCZ therapy in NIU.